Case study: Pulsed electric field ablation for salvage prostate cancer ablation - Katie Lattanzio; Khalid Alkhatib; Tom Guzzo; Daniel J. Lee; Phil Pierorazio; Trinity Bivalacqua; Ben Schurhamer (Urology Case Reports)
Pulsed Electric Field (PEF) ablation is an emerging non-thermal ablation device with previous uses in lung, liver and sarcoma cancers. We present a case of prostate cancer recurrence post-radiation managed with PEF ablation. Under transperineal guidance, targeted PEF was delivered to the area of concern on previous biopsies and PSMA. In follow up the patient had a marked decline in PSA levels and resolution on follow-up PSMA. The patient experienced no significant side effects, preserving urinary continence and sexual function. These outcomes underscore PEF ablation's potential as a safe and effective salvage therapy with minimal impact on quality of life.